2016
DOI: 10.1002/cptx.13
|View full text |Cite
|
Sign up to set email alerts
|

Basic Techniques in Mammalian Cell Tissue Culture

Abstract: Cultured mammalian cells are used extensively in cell biology studies. It requires a number of special skills in order to be able to preserve the structure, function, behavior, and biology of the cells in culture. This unit describes the basic skills required to maintain and preserve cell cultures: maintaining aseptic technique, preparing media with the appropriate characteristics, passaging, freezing and storage, recovering frozen stocks, and counting viable cells. © 2016 by John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…A uniform cell suspension (10 μl) was mixed with 10 μl of 0.4% trypan blue (18). The cells were left for ∼3 min for the cells to stain and loaded onto a chamber of a Countess slide for examination.…”
Section: Cell Cultivationmentioning
confidence: 99%
“…A uniform cell suspension (10 μl) was mixed with 10 μl of 0.4% trypan blue (18). The cells were left for ∼3 min for the cells to stain and loaded onto a chamber of a Countess slide for examination.…”
Section: Cell Cultivationmentioning
confidence: 99%
“…For viscous flows, however, the momentum deficit due to the viscous effect substantially changed the static pressure fields, which eventually generated main stream flows in the closed loop channel. Therefore, it can be concluded that (1) the present flow is initially characterized by shear-driven flows and shows transient phenomena, (2) as the flows reach steady state, the vortex flows are generated in the diode pumping region and the momentum deficit due to viscosity makes the change of static pressure in the downstream direction, and (3) the pressure-driven flows are generated under the steady-state condition along the closed-loop channel.…”
Section: B Cfd Simulation Of Diode Pump-driven Fluidicsmentioning
confidence: 96%
“…All cell culture experiments were performed in an aseptic condition within a class II Biosafety cabinet (Thermo EC, USA). Cells were sub-cultured at a split ratio of 1:3 after treatment with 0.25% Trypsin-EDTA solution [17] followed by addition of complete cell culture medium containing Dulbecco's Modified Eagle's Medium (Invitrogen) supplemented with 10% heat inactivated fetal bovine serum (Invitrogen), 100 units penicillin/ml, 10 microgram streptomycin/ml and 25 microgram of amphotericin B/ml (Sigma-Aldrich). CA24 (ATCC-VR-583) was procured from the American Type Culture Collection (ATCC, USA).…”
Section: Cells and Virusmentioning
confidence: 99%